Distribution, identification and ecology of Phortica genus (Diptera: Drosophilidae) in Spain - Mikel Alexander González; Marcos López-de-Felipe; Sergio Magallanes; Pedro María Alarcón-Elbal; Carlos Barceló; Yasmina Martínez-Barciela; Alejandro Polina; Ana María García-López; Laura Blanco-Sierra; Miguel A. Peláez Guerra; Sarah Delacour; Jordi Figuerola; et al. (International Journal of Veterinary Science and Medicine)
The genus Phortica (Diptera: Drosophilidae) includes five species of small flies in Europe. Phortica variegata, the zoophilic fruit fly, is the main vector of Thelazia callipaeda, a zoonotic parasite that is rapidly spreading througout Europe. Despite extensive studies on thelaziosis in animals and humans, there is limited knowledge about the geographical distribution and hovering activity of these vector flies. In 2023, 1,462 Phortica flies were sampled across 12 Spanish provinces, providing new records of Phortica variegata and Phortica oldenbergi. Surprisingly, P. oldenbergi, previously considered a rare Afrotropical species, was prevalent in most regions sampled in Spain. However, Phortica semivirgo was not collected. The abundance of Phortica spp. correlated positively with altitude and certain tree species. Rural oak-wooded areas in central and northern Spain showed the highest densities of P. variegata. Both drosophilid species were analysed morphologically and molecularly, providing new morphological descriptors and sequence barcodes for species identification. Phylogenetic analysis based on COI sequences, showed P. oldenbergi grouped with Asian origin Phortica species, while P. variegata in America was closer to Spanish sequences than those from other European countries. The hovering activity of P. variegata causes significant discomfort to humans during outdoor activities. This paper also reviews the historic records of P. variegata, P. semivirgo and P. oldenbergi in Spain over the last 90 years. This study enhances the understanding of the distribution, identification, ecology, and behaviour of these zoophilic flies in Europe.